Characterization of gliadin, secalin and hordein fractions using analytical techniques - Monika Rani (Nature Portfolio, 2021)
Abstract Prolamins, alcohol soluble storage proteins of the Triticeae tribe of Gramineae family, are known as gliadin, secalin and hordein in wheat, rye and barley respectively. Prolamins were extracted from fifteen cultivars using DuPont protocol to study their physiochemical, morphological and structural characteristics. SDS-PAGE of prolamins showed well resolved low molecular weight proteins with significant amount of albumin and globulin as cross-contaminant. The β-sheet (32.72–37.41%) and β-turn (30.36–37.91%) were found higher in gliadins, while α-helix (20.32–28.95%) and random coil (9.05–10.28%) in hordeins. The high colloidal stability as depicted by zeta-potential was observed in gliadins (23.5–27.0 mV) followed secalins (11.2–16.6 mV) and hordeins (4.1–7.8 mV). Surface morphology by SEM illustrated the globular particle arrangement in gliadins, sheet like arrangement in secalins and stacked flaky particle arrangement in hordeins fraction. TEM studies showed that secalin and hordein fractions were globular in shape while gliadins in addition to globular structure also possessed rod-shaped particle arrangement. XRD pattern of prolamin fractions showed the ordered crystalline domain at 2θ values of 44.1°, 37.8° and 10.4°. The extracted prolamins fractions showed amorphous as well as crystalline structures as revealed by XRD and TEM analysis. Space saving hexagonal molecular symmetry was also observed in TEM molecular arrangement of prolamins which has profound application in development of plant-based polymers and fibres.